Presentation - Spoken and/or written language? Reflections on acquisition and teaching of the Portuguese language from a decolonial perspective - Barbosa do Rêgo Barros, Isabela; Pereira Daróz, Elaine; Ferreira Caçador Anastácio, Zélia; Soares da Silva, Maria Rennally (Revista Letras Raras, 2024)
Presentation _Spoken and/or written language? Reflections on acquisition and teaching of the Portuguese language from a decolonial perspective